Dental biosafety from pediatric dentists’ perception in times of COVID-19, Lima, 2020 - Solís Romero, Denny Liliana (2022)
Objective: To describe pediatric dentists’ perceptions regarding dental biosafety in times of COVID-19 in Lima, 2020.Materials and methods: A qualitative, phenomenological and content-analysis study. In-depth semi-structured interviews were conducted with 18 pediatric dentists through the Zoom videoconferencing platform, following the guidelines described in a guide and after obtaining the pertinent virtual informed consent. ATLAS.ti software version 8.4 was used for data analysis, where all the verbatim files of each interview were uploaded.Results: Pediatric dentists perceived themselves to be professionally empowered with knowledge about biosafety measures. Moreover, they highlighted the mastery of various techniques such as mouthwash, use of personal protective equipment, control of aerosols, social distancing between patients and disinfection of environments, which are essential for patient safety. They also reported that biosafety regulations are somewhat confusing, unclear, and lack a pediatric approach. Conclusions: Pediatric dentists are strategic human resources for healthcare because they gained biosafety knowledge as part of their professional education and received training on new biosafety regulations in the context of the COVID-19 pandemic. It is important to standardize the criteria and approaches in the model of care for pediatric dentistry and guarantee the conditions for the sustainability of this professional practice.